Blue Economy Financing: Sustainable Aquaculture in Indonesia - Lestari, Dhoya Safira Tresna; Purwanto, Setiyo (Quantitative Economics and Management Studies, 2025)
The aquaculture sector is a strategic component in Indonesia's marine development, but its sustainability faces serious challenges such as environmental degradation, limited access to finance, and low adoption of environmentally friendly practices. This study aims to analyze the influence of Blue Economy Financing (BEF) on Sustainable Aquaculture (SA), considering the mediating role of environmental, social and governance (ESG) factors. The study uses an explanatory quantitative approach using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) method, based on sample data of 120 seaweed farmers in the coastal area of South Sulawesi. The results of this study show that BEF strongly supports the sustainability of sustainable aquaculture. However, ESG mediation has no effect on increasing the role of BEP in the development of SA. Although the model has adequate predictive capabilities for sustainability, the influence of BEF on ESG is not strong enough to explain and convince the public, investors and the government for the development of SA. To optimize the role of ESG as a catalyst for sustainability, supporting strategies such as institutional strengthening, technological innovation, and integrated policy interventions are needed. This research confirms that BEF is an important instrument in encouraging sustainability transformation in the aquaculture sector. These findings provide practical implications for the development of a more adaptive blue financing scheme in supporting Indonesia's sustainable marine development agenda.